Missed chances? Sequestration and non-sequestration of alkaloids by moths (Lepidoptera). (May 2023) - Petzel-Witt, Silvana; Wunder, Cora; Pogoda, Werner; Toennes, Stefan W.; Mebs, Dietrich
Abstract: Some butterflies and moths sequester and retain noxious phytochemicals for defence against predators. In the present study, three moth species, the garden tiger moth, Arctia caja, the death hawk moth, Acherontia atropos, and the oleander hawk moth, Daphnis nerii, were tested whether they sequester alkaloids from their host plants. Whereas A. caja consistently sequestered atropine from Atropa belladonna, also when atropine sulfate was added to the alkaloid-free diet of the larvae, A. atropos and D. nerii were found to be unable to sequester alkaloids, neither atropine nor eburnamenine from Vinca major, respectively. Instead of acquiring toxicity as chemical defence, nocturnal lifestyle and cryptic attitudes may improve their chances of survival. Graphical abstract: Image 1 Highlights: Larvae of three moth species were reared on host plants containing alkaloids. One of them, Arctia caja, sequesters and stores the alkaloid atropine. The moth may achieve chemical protection against predators. Two other moths, Acherontia atropos and Daphnis nerii do not sequester alkaloids. Therefore, they lack toxic alkaloids useful for chemical defense.